Improvement of the methodology of justification of design decisions for creating an image video - Potrashkova, Lyudmyla (Technology audit and production reserves, 2021)
The object of research is the process of substantiating design decisions for creating an image video at the pre-production stage. An insufficiently thought-out image video can cause a negative effect that is destructive for the image of the advertised subject. Therefore, every decision made when creating an image video at the pre-production stage must be substantiated on the basis of a multidimensional analysis. In this study, the content of the traditional stages of the pre-production stage has been improved by taking into account the specifics of the image video, as well as by using the questionnaire method: the image of the advertised entity is considered as a system consisting of a set of specific qualitative characteristics of the relevant person or organization; the main characteristics of the video being developed are determined by the results of a survey of the target audience. The result of the study was an improved methodology for substantiating design decisions for creating an image video, which features: 1) justification of the list of components of the customer's image that need to be advertised; 2) application of the questionnaire method to determine the main characteristics of the video being developed, such as: type of video, graphic style, color scheme, duration, prevailing ways of presenting information. The proposed methodology is concretized to substantiate decisions in the process of creating an image video of an educational program with a dual form of training. The components of the image of the educational program that need to be advertised in the video are determined based on the results of a survey of applicants and students. Expert assessment was carried out using the ranking method. When processing the results of the questionnaire, a difference was revealed in the judgments of different groups of respondents, which became the basis for setting the task of advertising several components of the image of the educational program. The use of the proposed methodology allows making more informed decisions regarding the content and form of an image video, which will contribute to the establishment of effective relationships between the advertised subject and its stakeholders.